Mengungkap Hubungan Antara Infrastruktur Layanan Publik dan Kinerja Pemerintah Daerah di Indonesia - Muhamad Lutfi Azizan; Septiano Alvian Ismau; Rizki Artinio Permana Putra; Putri Amalia; Ali Ibrahim; Zurnan Alfian (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
Local government performance and the availability of public service infrastructure are two important indicators in assessing the success of regional development. This study aims to examine the relationship between the number of post offices as an indicator of public service infrastructure and the performance scores of provincial governments in Indonesia. The data used are from the 2007 Transportation Statistics (number of post offices per province) and the 2016 Ministry of PAN-RB report (local government performance scores). The results of the analysis indicate that provinces with better public service infrastructure tend to have higher government performance scores. Although not all correlations are strong and significant, these findings indicate the importance of equal infrastructure to support effective governance.